Division of Lacustrine Environment and Significance for Shale Oil Exploration: A Case Study of the Third Member of Shahejie Formation in Dongying Sag - He Zhao; Hongliang Wang; Nana Mu (Energies, 2025)
The third member of the Shahejie Formation (Es3) in Dongying Sag is noteworthy for its abundance of laminated shale, considerable thickness, and high organic matter content, with carbonate interbeds playing a crucial role in reservoir properties. The salinity and pH of water influence the change of sedimentary environment and the mineral composition of sediment, thereby affecting the distribution characteristics of carbonate interbeds. Based on geochemical data from 8721 samples in the Dongying Sag, this study systematically analyzed the salinity and pH characteristics. This study is the first to develop an environmental zoning framework based on aqueous medium characteristics of aqueous media, and the favorable shale oil enrichment areas in Es3 were identified by integrating carbonate mineral content analysis. The results showed that the lower part of Es3 is dominated by a zone with high salinity–middle pH, and middle salinity–high pH with rich carbonate. Combining the development of carbonate interbeds, it is speculated that the sweet spots in Es3 are high salinity–middle pH and middle salinity–high pH. The favorable areas are concentrated in the lower part of Es3, including the western and northeastern parts of the Lijin Sub-Sag and the northern gentle slope of Guangrao. It provides a novel perspective on shale oil exploration through lacustrine environmental zonation.